Phenomenon of Altruism: Current Youth Perceptions From the Historical and Sociological Perspectives - Natalya L. Antonova; Ilia E. Levchenko; Natalia G. Popova (Changing Societies & Personalities, 2025)
Perceptions held by youth regarding altruism are analyzed using the findings of empirical research. The article proposes a historical and sociological conceptualization of the phenomenon of altruism, which is interpreted as a set of actions and interactions between individuals and groups intended to benefit another person. Drawing on interview materials (n = 34), the authors argue that the younger generation is oriented toward prosocial activities (banal altruism) in everyday practices and believe altruists to be selfless, responsive, caring, well-bred, and kind people. Young people adopt the Golden Rule of morality, believing that altruistic acts promote social solidarity and justice. A small proportion of youth exhibit egocentric attitudes, which can be attributed to rationalized thinking, fear, and negative experiences of prosocial activities. The informants are selective in their willingness to engage in altruistic acts, focusing primarily on personal, reciprocal, public, and non-institutional altruism. The study revealed that youth consider altruism to be a form of local proactive normative behavior, which indicates the social potential of youth to reproduce social order and social sustainability through altruistic practices in everyday life.